The Powder Monkey - Rylance, Maureen (Oxford Oxford University Press, 2014)
It is 1805 and 11-year-old Harry dreams of being in the navy in The Powder Monkey. One day, delivering supplies to a ship, he is accidentally hit on the head. When he wakes, his dream has become a nightmare TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Readers (Elementary)